TIGAR deficiency induces caspase-1-dependent trophoblasts pyroptosis through NLRP3-ASC inflammasome - Guo, Junjun; Zhou, Meijuan; Zhao, Man; Li, Shuxian; Fang, Zhenya; Li, Anna; Zhang, Meihua (Frontiers in Immunology, 2023)
Gestational diabetes mellitus (GDM), a common complication of pregnancy, is risky for both mother and fetus. Previous studies about TP53-induced glycolysis and apoptosis regulator (TIGAR) focused on the occurrence and development of cancer, cardiovascular disease, and neurological disease, however, it is still unclear whether TIGAR plays a regulatory role in gestational diabetes mellitus (GDM). Utilizing HG exposure, we explored the role of TIGAR in oxidative stress limitation, excessive inflammatory toxicity defense, and pyroptosis prevention. TIGAR was up-regulated in vivo and in vitro under HG condition, and loss of TIGAR increased ROS in trophoblast cells which drove a phenotypic switch and hindered the capacity of migration, invasion, and tube formation. This switch depended on the increased activation of NLRP3-ASC-caspase-1 signaling, which caused a distinctive characteristic of pyrotosis, which could finally be reverted by antioxidant treatment (NAC) and receptor block (MCC950). Collectively, trophoblast pyroptosis is an upstream event of TIGAR deficiency-induced inflammation, which is promoted by ROS accumulation through NLRP3-ASC inflammasome.